First-Principles Investigation on the Adsorption and Diffusion of Oxygen at the B2(110)–O(001) Interface in Ti2AlNb Alloys - Ming Zhang; Hongping Xiang; Lin Xu; Aihan Feng; Shoujiang Qu; Daolun Chen (Metals, 2024)
The adsorption and diffusion of oxygen at the B2(110)[<semantics><mover accent="true">1¯</mover></semantics>11]||O(001)[1<semantics><mover accent="true">1¯</mover></semantics>0] interface in Ti2AlNb alloys were investigated via first-principles calculations. Only a 2.6% interfacial mismatch indicates that B2(110)–O(001) is basically a stable coherent interface. The calculated adsorption energies and diffusion energy barriers show that oxygen prefers to occupy the Ti-rich interstitial sites, and once trapped, it hardly diffuses to other interstitial sites, thus promoting the preferential formation of Ti oxides. Under the premise of a Ti-rich environment, a Nb-rich environment is more favorable for oxygen adsorption than an Al-rich environment. The electronic structures suggest that O 2p orbitals mainly occupy the energy region below −5 eV, bonding with its coordinated atoms of Ti, Al, and Nb. However, Al 3p and Nb 4d orbitals near the Fermi level couple with sparsely distributed O 2p orbitals, forming anti-bonding, which is not conducive to oxygen adsorption. Because Nb 4d electrons are more localized than Al 3p electrons are, Nb–O anti-bonding is weaker. O–Ti has almost no contribution to anti-bonding, suggesting good bonding between them. This is consistent with the experimental observations that TiO2 is the main oxidation product.